Characterization of the Competitive Pneumocin Peptides of Streptococcus pneumoniae - Wholey, Wei-Yun; Abu-Khdeir, Maha; Yu, Emily A.; Siddiqui, Saher; Esimai, Ogenna; Dawid, Suzanne (Frontiers in Cellular and Infection Microbiology, 2019)
In the polymicrobial environment of the human nasopharynx, Streptococcus pneumoniae (pneumococcus) competes with other members of the microbial community for limited nutrients in part by secreting small peptide bacteriocins called pneumocins. Pneumocin production is controlled by a quorum sensing system encoded by the blp locus. Although the locus is found in all pneumococci, there is significant variability in the repertoire of pneumocins and associated immunity proteins encoded in the Bacteriocin Immunity Region (BIR) and in the presence or absence of a functional Blp transporter. Strains without an active Blp transporter are inactive in plate overlay assays and rely on a homologous transporter that is only produced during brief periods of competence to stimulate the blp locus and secrete pneumocins. The variability of the locus suggests that selective pressure is influencing the content to promote the optimal competitive environment. Much of the variability in the blp locus has been described at the genome level; the phenotypic activity attributable to the various BIR genes has not been fully described. To examine the role of the predicted pneumocin peptides in competition, 454 isolates were screened for competence independent blp pheromone secretion using plate assays. Active strains were characterized for inhibition, BIR content, BlpC pherotype and serotype. Deletion analysis on inhibitory strains demonstrated that BlpI and BlpJ peptides function as a two-peptide bacteriocin and that BlpIJ immunity is encoded by the co-transcribed blpU4/5 genes. BlpIJ secretion promotes inhibitory activity against the majority of pneumococcal isolates when expressed in a Blp transporter intact background. Intermediate levels of competition in biofilms were noted when BlpIJ containing strains carried the non-functional Blp transporter. Based on genome data, the combination of BlpIJ in a Blp transporter intact strain is surprisingly rare, despite clear advantages during colonization and biofilm growth. In contrast, we show that the blpK/pncF operon encoding the single-peptide pneumocin BlpK and its immunity protein is found in the majority of isolates. Unlike, BlpIJ and BlpK were shown to promote a limited spectrum of inhibition due in part to immunity that is independent of activation of the blp locus.